Integrated enzymes activity and transcriptome reveal the effect of exogenous melatonin on the strain degeneration of Cordyceps militaris - Zu, Zhichao; Wang, Siqi; Zhao, Yingming; Fan, Wenli; Li, Tianlai (Frontiers in Microbiology, 2023)
As a valuable medicinal and edible fungus, Cordyceps militaris has been industrialized with broad development prospects. It contains a lot of bioactive compounds that are beneficial to our health. However, during artificial cultivation, strain degeneration is a challenge that inhibits the industrialization utility of C. militaris. Exogenous melatonin (MT) can scavenge for reactive oxygen species (ROS) in fungus and can alleviate strain degeneration. To establish the significance and molecular mechanisms of MT on strain degeneration, we investigated the third-generation strain (W5-3) of C. militaris via morphological, biochemical, and transcriptomic approaches under MT treatment. Morphological analyses revealed that colony angulation of C. militaris was significantly weakened, and the aerial hypha was reduced by 60 μmol L–1 MT treatment. Biochemical analyses showed low levels of ROS and malondialdehyde (MDA), as well as increasing endogenous MT levels as exogenous MT increased. RNA-Seq revealed that compared with the control, several antioxidant enzyme-related genes were up-regulated under 60 μmol L–1 MT treatment. Among them, glutathione s-transferase genes were up-regulated by a factor of 11.04. In addition, genes that are potentially involved in cordycepin, adenosine and active compound biosynthesis for the growth and development of mycelium were up-regulated. Collectively, these findings provide the basis for further elucidation of the molecular mechanisms involved in C. militaris strain degeneration.